Dynamical Systems and Their Applications (DSTA) — In Memory of Prof. Dr. José A. Tenreiro Machado (MDPI - Multidisciplinary Digital Publishing Institute, 2024)
This volume focuses on the modeling and control of dynamic systems. It gathers linear and nonlinear dynamics, systems modeling, advanced control theory, complex systems, fractional calculus, fractals, entropy, information theory, chaos, self-organization, and criticality contributions. This volume presents the manuscripts of the Special Issue by Mathematics as a tribute to Professor J. A. Tenreiro Machado, who unexpectedly passed away on October 6, 2021. Studies regarding fractional calculus represent a significant part of this volume, with the modeling and control of dynamic systems being the most represented. Moreover, there is one article that studies the dynamics of a fractional-order discrete-time susceptible–infected–recovered epidemic model and another one that presents an analysis of one of Professor J. A. Tenreiro Machado's works serving as a basis for a deeper reflection on the origins of fractional behaviors and their modeling.This volume reflects, to a great extent, the scientific areas Prof. Tenreiro Machado worked in and also enhances the importance of modeling and control of dynamic systems in science and engineering. Guest Editors thank Mathematics for their support in launching this Special Issue.